2021
DOI: 10.1128/aem.01160-21
|View full text |Cite
|
Sign up to set email alerts
|

Viral Characteristics of the Warm Atlantic and Cold Arctic Water Masses in the Nordic Seas

Abstract: Nordic Seas are the subarctic seas connecting the Arctic Ocean and North Atlantic Ocean with complex water masses, experiencing an abrupt climate change. Though the knowledge of the marine virosphere has been expanded rapidly, the diversity of viruses and their relationships with host cells and water masses in the Nordic Seas remains to be fully revealed. Here we establish the Nordic Seas DNA viromes (NSVs) dataset of 55,315 viral contigs including 1,478 unique viral populations from seven stations influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 96 publications
1
11
0
Order By: Relevance
“…In the present study, Myoviridae , Podoviridae , Siphoviridae , and Herelleviridae were the most common bacteriophages identified, consistent with their common occurrence in oceans [ 55 ]. The presence of Pelagibacter phage HTVC008M and Puniceispirillum phage HMO-2011, including the Pelagibacter phage group, suggests that the SAR11 bacterial group is abundant in the Arctic Ocean [ 56 ]. The co-occurrence of various phages with various bacteria indicates that phages may be capable of infecting multiple host bacterial ecotypes in warm- and cold-water environments [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, Myoviridae , Podoviridae , Siphoviridae , and Herelleviridae were the most common bacteriophages identified, consistent with their common occurrence in oceans [ 55 ]. The presence of Pelagibacter phage HTVC008M and Puniceispirillum phage HMO-2011, including the Pelagibacter phage group, suggests that the SAR11 bacterial group is abundant in the Arctic Ocean [ 56 ]. The co-occurrence of various phages with various bacteria indicates that phages may be capable of infecting multiple host bacterial ecotypes in warm- and cold-water environments [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the diversity of Mimiviridae structure and, a subsequent, broad range of hosts and environments compared to the reference sequences of known viral genomes [ 58 ]. In particular, Mimiviridae species are frequently found in low-temperature seawater, such as in the Arctic [ 59 , 60 ], which is likely related to the frequency and types of hosts. Indeed, our results showed that Mimiviridae and Pandoraviridae were significantly and positively correlated with specific EPC taxa, namely, Aureococcus anophagefferens (pOTU#0) increased rapidly in June, as did Megavirus chiliensis (vOTU#69) and Chrysochromulina ericina virus (vOTU#26) also increased.…”
Section: Discussionmentioning
confidence: 99%
“…2 to 4 ; Fig. S2 and S3 ), suggesting that marine viruses in general are still largely uncharacterized ( 30 34 ). In general, the spatiotemporal dynamics of abundance, community structure, and diversity of the viral assemblages ( Fig.…”
Section: Discussionmentioning
confidence: 99%